Probing deeper into the risks of slips, trips and falls for an ageing rail passenger population: applying a systems approach - Waterson, Patrick E.; Kendrick, Victoria L.; Ryan, Brendan; Jun, Thomas; Haslam, Roger A. (Institution of Engineering and Technology, 2016)
In this study, the authors report the findings from a study of the contributory factors leading to slips, trips and falls (STFs) amongst elderly passengers at train stations and how these are likely to change in the future over the medium to long term (the period 2035–2050). Their data draws on: stakeholder interviews with rail personnel and elderly passengers; a set of station observations carried out across the UK; and, a survey of the views of station managers. The findings point to a set of 22 contributory factors covering aspects of organisational, station environment and passenger (individual) influence on STFs. Amongst the factors which most concern station managers at the present and over the next few decades are: rushing behaviour on train platforms; the consumption of alcohol by passengers; aspects of station design (e.g. flooring); and, training for station staff as regard the risks of STFs. The authors summarise their findings in the form of a systems model which highlights priorities with regard to STFs in terms of all of the stakeholders taking part in the study. A final section discusses a set of issues which might form the basis for a future agenda for research and practice in this area.